Exploring the Impact of Sports And Culture on Students in Delta Tertiary Institutions in Nigeria (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
The study utilized a structured questionnaire titled “Sports and Culture Impact Questionnaire (SCIQ)” as the primary instrument for data collection. The questionnaire comprised four sections. Section A gathered demographic information such as age, gender, institution, and year level. Section B measured sports participation, focusing on the frequency, type, and level of involvement using a 5-point Likert scale. Section C assessed cultural engagement by examining participation in activities such as music, dance, drama, festivals, and language clubs, including self-perceived cultural identity. Section D evaluated student outcomes through self-reported academic performance, social cohesion, and psychological well-being. To ensure content validity, the instrument underwent expert review by two lecturers in Physical and Health Education and two lecturers in Sociology and Cultural Studies. Their feedback helped refine the clarity and relevance of the items, ensuring alignment with the study’s objectives. Reliability was confirmed through a pilot study conducted with 30 students from a non-selected tertiary institution. Cronbach’s alpha values were satisfactory: 0.82 for sports participation, 0.79 for cultural engagement, and 0.85 for student outcomes, all exceeding the recommended 0.70 threshold. Data collection followed a systematic procedure. Institutional approval was first obtained, and informed consent was secured from all participants. Trained research assistants administered and retrieved the questionnaires in classrooms and campus common areas, with each participant completing the instrument within 15–20 minutes. Data were analyzed using SPSS version 28. Descriptive statistics summarized the demographic characteristics and key variables, while inferential statistics—including Pearson correlation, multiple regression, t-tests, and ANOVA—were used to test relationships and group differences, with significance set at p < 0.05..